2021
DOI: 10.3390/su13126814
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the EU IUU Regulation on the Sustainability of the Thai Fishing Industry

Abstract: In recent years, the implementation of and compliance with general values such as the protection of human rights, labor, environment, and democracy has become a very important agenda in global trade policy. The new Secretary General of the WTO emphasized her strong interest in the WTO negotiations in reforming various subsidies for fishing industries, which are to be concluded by the upcoming Twelfth MC (Ministerial Conference) in November 2021. Sustainability has become another critical issue in the internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thereby, the identified implications are distinguished within a temporal dimension (Ebrahim and Rangan, 2014;Nelson et al, 2014). However, the term impact assessment is often inconsistently defined and used for various purposes (Ebrahim and Rangan, 2014;Adebayo et al, 2016;European Commission, 2016;Wongrak et al, 2021). In this study, we distinguish between the three key concepts: output, outcome, and impact, constituting the concept of the impact pathway.…”
Section: Fundamentals On Impact Assessmentsmentioning
confidence: 99%
“…Thereby, the identified implications are distinguished within a temporal dimension (Ebrahim and Rangan, 2014;Nelson et al, 2014). However, the term impact assessment is often inconsistently defined and used for various purposes (Ebrahim and Rangan, 2014;Adebayo et al, 2016;European Commission, 2016;Wongrak et al, 2021). In this study, we distinguish between the three key concepts: output, outcome, and impact, constituting the concept of the impact pathway.…”
Section: Fundamentals On Impact Assessmentsmentioning
confidence: 99%
“…The modern slavery scandal called for a rapid response from private-sector actors. The warning issued by the EU in 2015 resulted in a steep drop in the export value of seafood from Thailand to the EU, with values in 2018 reaching only a third of 2014 values (Wongrak et al, 2021). In the face of reputational risks and the imminent threat of losing business, companies with Thai Labour NGOs during the 'Modern Slavery' Reforms 585 supply chains in Thailand began outreach activities and actively sought partnerships with NGOs.…”
Section: The Partner Role With Multinational Corporationsmentioning
confidence: 99%
“…Despite the significance of these measures in improving seafood sourc ing for EU members and fishing practices in exporting countries (Leroy, Galletti and Chaboud 2016;Wongrak et al 2021), some IUU-caught fish is still being imported into the EU, in part due to shortcomings in the regulation and its implementation. For example, Okafor-Yarwood and Bel habib (2020) have shown that the EU failed to red-card countries with which it has major trade exchanges.…”
Section: Fish Imports Jurisdictionmentioning
confidence: 99%